Manajemen Keuangan Negara dalam Upaya Mewujudkan Pembangunan Berkelanjutan: Studi Kasus Implementasi Anggaran Berbasis Kinerja di Indonesia - Salsabillah, Nurfaizah; Tobing, Naomi Boru; Nurhafriza, R.; Pangestoeti, W (Penerbit Yayasan Daarul Huda Kruengmane, 2025)
Sustainable development is a global agenda that demands countries in the world, including Indonesia, to undertake transformation in state financial governance. One of the important strategies used by the Indonesian government is the implementation of performance-based budgeting. This article aims to analyze the role of state financial management, particularly through the application of performance-based budgeting, in supporting the achievement of sustainable development in Indonesia. The study used a qualitative approach with literature study and policy analysis as the primary methods. Study results show that performance-based budgeting has encouraged transparency, accountability, and effectiveness of state budget use, although it still faces various challenges in its implementation. The article recommends strengthening human resource capacity, integration of information systems, as well as stricter supervision and evaluation as strategic measures to strengthen the role of state financial management in supporting sustainable development.